An engineering approach towards a more discrete and efficient urinary drainage system. (January 2019) - Marzo, Alberto; Melis, Alessandro; Unger, Jaan; Sablotni, Robert; Pistis, Mauro; McCarthy, Avril D
Modern urinary catheter-to-leg-bag systems suffer from a number of shortcomings. Drainage tubing of current urinary leg bags is perceived as unnecessarily bulky compared to the indwelling catheters to which it is connected, and catheter designs are prone to the formation of biofilms, leading ultimately to encrustation and blocking. We used analytical and experimental engineering methodologies, aligned with current international (International Standards Organisation) and European standards, to optimise drainage tube size and flow efficiency and characterise tube kinking behaviour. Using computational fluid dynamics, we studied the influence of modern Foley catheter design on urodynamics and explored its potential influence on biofilm formation and encrustation. Results indicate that tubing diameters could be reduced by 40%–50% and still satisfy current International Standards Organisation flow rate standards for leg bags; this might also reduce the likelihood of tube kinking. The computational study showed how current catheter design may promote the development of lower velocity recirculating flows and high shear in proximity of regions known to be affected by bacterial adhesion and biofilm formation. If confirmed, these findings will give manufacturers greater flexibility to develop less obtrusive and more encrustation-resistant products for end users.